2015
DOI: 10.1371/journal.pone.0141087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Chemistry, Pipe Material and Stagnation on the Building Plumbing Microbiome

Abstract: A unique microbiome establishes in the portion of the potable water distribution system within homes and other buildings (i.e., building plumbing). To examine its composition and the factors that shape it, standardized cold water plumbing rigs were deployed at the treatment plant and in the distribution system of five water utilities across the U.S. Three pipe materials (copper with lead solder, CPVC with brass fittings or copper/lead combined pipe) were compared, with 8 hour flush cycles of 10 minutes to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 86 publications
(114 reference statements)
7
106
2
Order By: Relevance
“…; Ji et al . ). However, the impact of the material may be less intense than other studied parameters such as utility in full‐scale distribution system waters (Ji et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Ji et al . ). However, the impact of the material may be less intense than other studied parameters such as utility in full‐scale distribution system waters (Ji et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the impact of the material may be less intense than other studied parameters such as utility in full‐scale distribution system waters (Ji et al . ). In our pilot scale study, the control copper and PEX materials showed similar composition within the most abundant bacterial groups, confirming our earlier findings from the full‐scale system of the same building (Inkinen et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…High throughput sequencing is a powerful tool for understanding the microbial ecology of premise plumbing, revealing diverse microbial community compositions in drinking water distribution systems across the globe (Chao et al, 2015; Delafont et al, 2014; Hong et al, 2010; Ji et al, 2015). A typical procedure for drinking water microbiome investigation includes application of universal primers targeting 16S rRNA genes for DNA amplification followed by high throughput sequencing, the result of which could demonstrate the presence or absence of genera containing potential OPPPs (Delafont et al, 2014; Gomez-Smith et al, 2015; Ji et al, 2015; Wang et al, 2013). Reported abundances of sequences belonging to these genera varied considerably across different samples.…”
Section: Detection Methodsmentioning
confidence: 99%
“…The core microbiome is considered to be a key component of the basic function of the holobionts, which is enriched, selected, and inherited through evolutionary processes (Lemanceau, Blouin, Muller, & Moënne-Loccoz, 2017). The core microbiomes are commonly used to reveal microbial species that are closely related to the health, growth, and physiology of the host plant and are currently widely used to describe the key species in human, soil, plant, lake, and wastewater treatment system (Chen, Wu, et al, 2018;Chen, Li, et al, 2018;Ji, Parks, Edwards, & Pruden, 2015;Turnbaugh et al, 2007;Zarraonaindia et al, 2015). However, the core microbiomes and their function in the tobacco aging process still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%